New frequency quadrupling techniques based on carrier suppression for high quality 60 GHz radio over fiber systems - Nael Ahmed Mohammed (School of Computer and Communication Engineering, University Malaysia Perlis, 2014)
Millimeter-wave (MMW) wireless networks in the 60 GHz unlicensed band have become a key technology for enabling multi-gigabit wireless access and provisioning of quality of service (QoS)-sensitive applications. However, numerous difficulties need to be solved in the 60 GHz wireless systems, the most important of which is the high air-link loss. This issue implies that many remote base stations (BSs) need to be deployed to cover a large area. Radio-over-fiber (RoF) technology, the integration of wireless and optical communication, has long been proposed as an ideal technology for solving these difficulties. Aside from numerous advantages, such as low propagation loss, low cost, large bandwidth, and immunity to electromagnetic interference, the RoF technology enables the shift of complexity from BSs to a central office by a centralized provision of the MMW carrier. In an RoF system, the high-quality generation of MMW signals with simple implementation is a key technique. Compared with the conventional electrical method, the optical method is preferable. In this thesis, we propose two new frequency-quadrupling approaches for the optical generation and downstream transmission of high-quality and data modulated 60 GHz signals on the basis of two parallel dual-drive Mach--Zehnder Modulators (DD-MZMs) and one integrated dual-parallel MZM (IDP-MZM). As a result of these proposed approaches, two newly designed optical MMW generation schemes are proposed. The first scheme uses two parallel DD-MZMs to generate a high-quality optical carrier suppression (OCS) MMW signal, whereas the second scheme uses only one IDP-MZM to generate a high-quality optical MMW signal without optical filter. A detailed theoretical analysis of the proposed frequency-quadrupling approaches is conducted. Moreover, explicit expressions of the optical sidebands suppression ratio (OSSR), radio frequency spurious suppression ratio (RFSSRR), and MMW current are given and can be utilized for the evaluation of the qualities of the generated optical and electrical MWW signals in back-to-back (B-T-B) transmission, as well as the transmission performance of the generated optical MMW signal over optical fiber. The simulation software, OptiSystem (version 9.0), is utilized to evaluate the performance of the proposed approaches. Good agreement is found between theory and simulation. By using the first approach, the simulation results show that a 60 GHz MMW signal can be generated from a 15 GHz RF oscillator with an OSSR of up to 39.4 dB and an RFSSRR exceeding 35 dB without optical or electrical filter when the extinction ratios of the two DD-MZMs are 25 dB. For the second approach, the simulation results show that the a 60 GHz MMW signal can be generated with an OSSR and an RFSSRR equal to 33.7 dB and 33.4 dB, respectively, without optical or electrical filter when the extinction ratio of the IDP-MZM is 30 dB. The influences of a number of non-ideal parameters, such as imperfect extinction ratio, RF driving voltage deviation, and phase shifting, on the performance of the proposed optical MMW generation schemes are examined through simulations. Results indicate that a slight deviation from the ideal values would not result in a significant degradation of the generated optical MMW signal. Finally, we build a RoF system through simulation, and the transmission performance of the generated optical MMW signals is presented. The eye pattern is clearly opened even when the optical MMW signal is transmitted over 60 km.